Experimental Investigation on the Production Behaviors of Methane Hydrate in Sandy Sediments by Different Depressurization Strategies. Issue 12 (23rd November 2018) - Lv, Tao; Li, Xiaosen; Chen, Zhaoyang; Sun, Duo; Zhang, Yu; Yan, Kefeng; Cai, Jing
Abstract: The depressurization method is one of the most promising methods for the exploitation of hydrate reservoirs and has been conducted in several field tests. In this work, the production behaviors of methane hydrate in sand sediments by different depressurization strategies were comparatively investigated using a cubic hydrate simulator (CHS) with a capacity of 5.832 L. The experimental conditions are based on the hydrate reservoirs parameters of the South China Sea. The results indicate that the hydrate dissociation rate is related to production pressure and heat conduction between the sediments and the surroundings. Some hydrate form again at the beginning of depressurization and the progress of hydrate dissociation during stable depressurization stage is basically along with the P−T curve. The cumulative amounts of gas production are almost the same, affirming it depends on the final depressurization amplitude, and less water produced when a short shut‐in period is conducted before hydrate dissociation. Compared to single‐step depressurization strategy, the multistep depressurization possesses a more well‐distributed gas production, and the sensible heat of sediments contributes less to hydrate dissociation. Despite the production period is longer, its temperature over the whole production process is higher, which has the potential to reduce the secondary hydrate formation and the damage of wellbore and sediments effectively in actual hydrate production. Abstract : Two different depressurization strategies were carried out to produce gas from the hydrate reservoir, respectively. The experimental conditions are based on the hydrate reservoirs parameters of the South China Sea. For the multistep depressurization strategy, the sensible heat of sediments contributes less to hydrate dissociation and the gas production is well‐distributed over the production process compared to single‐stage depressurization.